Hot Air Treatment Elicits Disease Resistance against Colletotrichum gloeosporioides and Improves the Quality of Papaya by Metabolomic Profiling. (4th August 2022) - Liu, Bo; Xue, Meiling; Zhou, Jiao; Zhang, Hongxia; Ren, Lili; Fan, Jianting
Abstract : Forced air heat treatment could induce defenses to protect fruit from pathogen attacks and has been applied as an alternative to methyl bromide for phytosanitary treatment before exportation. However, few studies were reported on the regulation mechanism of antifungal effect and delayed physiological disorders of papaya by heat treatment. Therefore, we aim to explore the fruit's resistance to pathogens and the inhibition of physiological disorders by metabolomic profiling. In our study, papaya fruits were treated with 47.2°C for 30, 60, and 90 min by forced hot air treatment. The disease resistance against Colletotrichum gloeosporioides, quality parameters, and metabolites of papaya fruits were measured during 10 days of storage after heat treatment by metabolomic profiling. Papaya fruits after 30 and 60 min heat treatment had higher firmness, a delayed degreening and yellowing (lower a value) process, and a higher lightness (L) and hue angle (h) during storage. Heat treatment also delayed ripening, inhibiting the growth of C. gloeosporioides and softening of papaya. Metabolites and enzymes inhibited ROS scavenging, depressed ABA-regulated respiratory, and activated phenylpropanoid metabolism. Our study provides a broad picture of fruit resistance to pathogens and the inhibition of physiological disorders by metabolomic profiling, which is induced by heat treatment.